2006
DOI: 10.1111/j.1748-0361.2006.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Diagnostic and Treatment Services for Acute Stroke in Frontier Counties in Montana and Northern Wyoming

Abstract: A stroke network model could enhance care and improve outcomes for stroke victims in frontier counties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…However, in rural areas and small communities these recommendations are often not implemented both in Europe 45 and the United States. 27 Of 58 hospitals in Montana and Wyoming, 79% were located in frontier counties. 27 Only 30% of the frontier hospitals met 6 to 10 of the Brain Attack Coalition criteria, compared to 67% of hospitals in the nonfrontier counties.…”
Section: Subacute Carementioning
confidence: 99%
See 1 more Smart Citation
“…However, in rural areas and small communities these recommendations are often not implemented both in Europe 45 and the United States. 27 Of 58 hospitals in Montana and Wyoming, 79% were located in frontier counties. 27 Only 30% of the frontier hospitals met 6 to 10 of the Brain Attack Coalition criteria, compared to 67% of hospitals in the nonfrontier counties.…”
Section: Subacute Carementioning
confidence: 99%
“…27 Of 58 hospitals in Montana and Wyoming, 79% were located in frontier counties. 27 Only 30% of the frontier hospitals met 6 to 10 of the Brain Attack Coalition criteria, compared to 67% of hospitals in the nonfrontier counties. Of 21 rural hospitals in Idaho, 29 none had a designated stroke team.…”
Section: Subacute Carementioning
confidence: 99%
“…Similar findings have been reported in Montana and northern Wyoming. 11 The implications of these findings for stroke outcomes in the Northwest region are sobering. Following the stroke continuum of care model, without use of EMS prehospital stroke screening tools and advance notification of ED arrival, medical staff and equipment cannot be prepared for timely evaluation and treatment of patients; without the availability of written stroke protocols in the ED and hospital, personnel may not provide timely and appropriate care to patients with stroke; and ultimately without timely and appropriate acute care, patients with stroke are not eligible for appropriate interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, acute stroke care capacity was lower in frontier hospitals compared with nonfrontier hospitals in Montana and northern Wyoming. 11 Closer proximity to optimal stroke care (through designated stroke centers) has been shown to be associated with lower mortality. 8 Given the known disparities that exist in rural and frontier areas, the Northwest Regional Stroke Network (NWRSN) wanted to assess the specific needs in our region to ultimately provide targeted and strategic interventions.…”
mentioning
confidence: 99%
“…In rural Australia, for example, over 90% of hospitals have 24-hour access to CT scanning, but residents have to travel, on average, about 100km. A study carried out in Montana and Northern Wyoming by Okon et al (2006) revealed that only 39% of hospitals had 24-hour CT capabilities. A study in China by Liu et al (2007) showed the use of CT in rural areas to be "low" compared to urban areas, but exact data are not available.…”
mentioning
confidence: 99%